Innovation and interdisciplinary solutions for underserved areas : first International Conference, InterSol 2017 and Sixth Collogue National sur la Recherche en Informatique et ses Applications, CNRIA 2017, Dakar, Senegal, April 11-12, 2017, Proceedings /: first International Conference, InterSol 2017 and Sixth Collogue National sur la Recherche en Informatique et ses Applications, CNRIA 2017, Dakar, Senegal, April 11-12, 2017, Proceedings. (2018) - Unknown
No abstract available